Avaliação tóxica, citotóxica e mutagênica de arilaminonaftoquinonas sintéticas - Freitas, Josivany Valério de (2011)
The search for new anticancer agents has become increasingly necessary, with a view to increased efficiency and reduced cytotoxic effect on normal tissues. In this perspective, quinones which are classified according to the aromatic system in its present structure, bearing a ring the naphthoquinones naphthalenic characteristic, have been extensively studied in recent decades due to their bioreductive properties and participation in oxidative stress. Toxicological studies for testing acute toxicity, cytotoxicity, genotoxicity and antigenotoxicity of various substances, especially when aiming at producing new medicines, are performed by bioassays that evaluate the effects of the agent tested on the cell and genetic material. We propose to evaluate the toxicity, cytotoxicity and mutagenicity of arilaminonaftoquinones 1, 2 and 3 by synthetic determination of the LD50 in mice, cytotoxicity against Artemia salina larvae and the micronucleus. The test for LD50 determining was conducted in Swiss albino mice (Mus musculus) in which mice with body mass index between 25-45g, were divided into experimental groups (n = 10) and treated separately, with arilaminonaftoquinones solution of 1, 2 and 3 DMSO/H2O in concentrations of 200, 500 and 1000 mg / kg, and with the negative control (CN-0.9% saline solution) intraperitoneally in experimental casual.The lethality test to larvae of the A. saline was performed according to the method of Meyer (Meyer et al., 1982), simplified. The samples were dissolved in DMSO solution and supplemented with artificial sea water, this solution were prepared dilutions. Metanauplius larval stage (10 units) were added to each tube containing the dilutions and the cultures were incubated for 24 hours. DMSO controls (NC) and lapachol + DMSO (CP) were included in the test. O micronucleus test was performed in vivo in bone marrow of Swiss albino mice (Mus musculus). To this end, we used young animals, males and females. For each of arilaminonaftoquinone tested the animals were randomly divided into twelve groups (3 animals of the same sex per cage), the same treatment was applied to a group of males and a group of females. For each of the six arilaminonaftoquinones groups received by gavage, Arilaminonaftoquinone [50, 100 and 200mg.kg-1 mc] dissolved in DMSO. The other groups received cisplatin (3mg.kg mc-1, ip, CP), DMSO (0.005 mL.g mc-1, CS) or 0.9% NaCl (CN). Bone marrow was collected 24 hours after treatment for preparation of slides. For each animal was calculated the number of micronucleated polychromatic erythrocytes (PCEMN) in 2000 polychromatic erythrocytes (PCE) from bone marrow cells and the number of micronucleated erythrocytes normochromatic (NCEMN) in 2000 normochromatic erythrocytes (NCE) in peripheral blood. Cytotoxicity was evaluated by means of the PCE: NCE in 200 erythrocytes (PCE + NCE) in bone marrow, per animal. Statistical analysis was performed using the software Assistat ® 7.5. Statistical significance comparing data between different treatment groups was performed by ANOVA (analysis of variance) to a criterion and the Tukey test a posteriori the 5% probability. The obtained datas by the LD50 test and the front toxicity A. Salina, showed that arilaminonaftoquinones tested are classified as harmful and cytotoxic respectively. When the results of micronucleus test results show us that the animal groups treated with different concentrations of DMSO arilaminonaftoquinonas + did not differ significantly from the CS and CN ratio on the PCE: NCE and the frequency of MN, while the CP group decreased ratio of PCE: NCE (P <0.01) and increased frequency of PCEMN (P <0.01) compared to the control group, demonstrating the sensitivity of the assay to detect genotoxicity in vivo.